A new species of Meligethes Stephens from China and additional data on members of the M. chinensis species-complex (Coleoptera: Nitidulidae, Meligethinae) - Liu, Meike; Huang, Min; Cline, Andrew Richard; Sabatelli, Simone; Audisio, Paolo (Fragmenta entomologica, 2017)
Meligethes (Odontogethes) inexpectatus sp. n. is described from China, Sichuan Province. The new species is based on a female specimen previously incorrectly referred to as Meligethes scrobescens Chen, Lin, Huang & Yang, 2015, which was recently described from a series of male specimens collected in the same area. Both species belong to the taxonomically difficult species-group related to M. chinensis Kirejtshuk, 1979, including a dozen closely related species distributed throughout Nepal and SW and Central China. The true female of Meligethes scrobescens is also described, based on recently collected material from China (Hubei and Chongqing), including a series of male and female specimens. Diagnostic characters distinguishing the new species from all other known members of the M. chinensis species-group and species-complex are discussed, and their overall range distribution are depicted. Additional data on geographic distribution and larval ecology of some of the closely related species are also reported.